Hydrophilic Nanocomposite Films with a Fence-Structure-Induced Labyrinth Effect for Greenhouse Cooling and Light Enhancement - Shi, Shaoze (Langmuir : the ACS journal of surfaces and colloids, 2022)
In this paper, we reported a new kind of cooling and light-enhanced hydrophilic nanocomposite film (PE/JW-0.8%) with low-density polyethylene (LDPE) as the substrate. The wetting, photophysical, and mechanical properties of PE/JW-0.8% were tested. The emission band of the fluorescence centers at 420 nm, which is perfectly consistent with the absorption spectrum of plant photosynthesis. In addition, light can be scattered by PE/JW-0.8% to achieve a larger light distribution area. PE/JW-0.8% showed a good durability of hydrophilicity in the water rinsing test. Meanwhile, the elongation at the break of the film was significantly increased. Benefiting from the fence structure induced labyrinth effect, a maximum reduction of 6.7 °C in temperature monitoring for PE/JW-0.8% was observed in the detailed field experiments. Light intensity monitoring showed that light intensity in PE/JW-0.8% increased by a maximum of 57.1% compared to PE/LH. In the biological quality analysis of melon, it was found that the soluble sugar, soluble solid, and vitamin C content of melon increased by 13.34, 22.96, and 50.95%, respectively. In conclusion, these results confirm that PE/JW-0.8% has great application potential in the field of facility agriculture, buildings, and photovoltaic modules